Linear Correlation of Ba and Eu Contents by Hydrothermal Activities: A Case Study in the Hetang Formation, South China. (1st April 2019) - Chang, Chao; Fu, Qi; Wang, Xiaolin
Abstract : A significant linear correlation between Ba and Eu contents has been observed in a set of mudrock formations in the lower Cambrian Hetang Formation in South China. Combined with petrographic features and reinvestigation of published data obtained from the same laboratory, the analytical interference of Ba can be excluded as a main factor of this correlation. Electron microprobe analyses (EMPA) have indicated that Ba-rich minerals (hyalophane and cymrite) precipitated from hydrothermal fluids account for the total Ba content. It is evident that significant contribution of both Ba and Eu from hydrothermal fluids is the cause of this linear relationship, while this coexistence is ultimately controlled by their similar chemical properties and abundances in rock sequences along the fluid path. This interpretation was supported by similar linear Ba-Eu correlations retrieved from barite-bearing chert in another area of the Yangtze platform during the same geological period. Therefore, linear Ba-Eu correlations may be more common than previously thought in this area, where hydrothermal activities were active during the specific time interval.